(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the issue of developing the competence of future physics teachers in the process of theoretical training from a scientific and methodological perspective. Within the framework of the study, the essence of the concept of competence, its main types, and the theoretical foundations for their formation in the system of physics education are elucidated. Furthermore, innovative approaches aimed at developing the methodological, scientific, information-communication, and reflective competences of future teachers during theoretical training sessions are proposed. The article scientifically substantiates the stages of competence formation based on active learning technologies, interactive methods, problem-based learning, and an integrated approach. It also pays special attention to assessment and self-development mechanisms aimed at increasing the effectiveness of organizing theoretical training sessions. The research findings contribute to aligning the professional training of future physics teachers with modern educational requirements, enhancing their creative and analytical potential, and ensuring their thorough preparation for practical training.